Between-Subject and Within-Subject Variation of Muscle Atrophy and Bone Loss in Response to Experimental Bed Rest - Böcker, Jonas; Schmitz, Marie-Therese; Mittag, Uwe; Jordan, Jens; Rittweger, Jörn (Frontiers in Physiology, 2022)
To improve quantification of individual responses to bed rest interventions, we analyzed peripheral quantitative computer tomography (pQCT) datasets of the lower leg of 76 participants, who took part in eight different bed rest studies. A newly developed statistical approach differentiated measurement uncertainty UMeas from between-subject-variation (BSV) and within-subject variation (WSV). The results showed that UMeas decreased 59.3% to 80% over the two decades of bed rest studies (p < 0.01), and that it was higher for muscles than for bones. The reduction of UMeas could be explained by improved measurement procedures as well as a higher standardization. The vast majority (89.6%) of the individual responses pci exceeded the 95% confidence interval defined by UMeas, indicating significant and substantial BSV, which was greater for bones than for muscles, especially at the epiphyseal measurement sites. Non-significant to small positive inter-site correlations between bone sites, but very large positive inter-site correlation between muscle sites suggests that substantial WSV exists in the tibia bone, but much less so in the calf musculature. Furthermore, endocortical circumference, an indicator of the individual’s bone geometry could partly explain WSV and BSV. These results demonstrate the existence of substantial BSV bone, and that it is partly driven by WSV, and likely also by physical activity and dietary habits prior to bed rest. In addition, genetic and epigenetic variation could potentially explain BSV, but not WSV. As to the latter, differences of bone characteristics and the bone resorption process could offer an explanation for its existence. The study has also demonstrated the importance of duplicate baseline measurements. Finally, we provide here a rationale for worst case scenarios with partly effective countermeasures in long-term space missions.